Traveling Epizootic Waves of a Fox Rabies Model with Small Spatial Diffusion (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, to describe the spread of fox rabies, a degenerateSEI epidemic model with small spatial diffusion equipped by infectious foxesdue to rabies is investigated. In particular, the existence of traveling wavesis established by the geometric singular perturbation theory for the largerspeeds, while the non-existence of traveling wave is still derived for the smallerspeeds. Moreover, some numerical simulations are implemented to illustratethe propagation dynamics driven by traveling waves.